2011
DOI: 10.1590/s0102-77862011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration of irrigated apple trees and citrus from a water potential gradient approach in the leaf-atmosphere system

Abstract: The uptake of water from the roots of crops comes to being a physiological response of the plant to the water loss process through its stomata. Getting to know the daily transpiration rates throughout the phenological cycle allows for the application of the ideal amount of irrigation water at the right moment to maximize production with environmental protection. Since transpiration direct measurements at the field, mainly for trees in general, are to be of operational difficulty and relatively high cost we cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Such data are effectively applied in the cultivation of specific crops such as citrus fruits, for which it is desirable to manage individual trees (Maotani and Machida, 1977;Cohen and Fuchs, 1987;Pereira et al, 2011), and Japanese tea, about which there is frost damage concern (Suzuki et al, 1982).…”
Section: Targets According To Resolution In Agriculturementioning
confidence: 99%
“…Such data are effectively applied in the cultivation of specific crops such as citrus fruits, for which it is desirable to manage individual trees (Maotani and Machida, 1977;Cohen and Fuchs, 1987;Pereira et al, 2011), and Japanese tea, about which there is frost damage concern (Suzuki et al, 1982).…”
Section: Targets According To Resolution In Agriculturementioning
confidence: 99%
“…Singh et al (2020) showed that all the growth parameters, yield attributes and yield were significantly higher in the North-South sowing direction as compared to East-West. Net radiation is an essential key to assessing evapotranspiration and precise estimation for water resource management on a regional scale (Villa Nova et al, 2006;Ryu et al, 2008;Pereira et al, 2011). PAR absorption by canopy results in increased plants biomass and grain weight (Kooman and Haverkort, 1995;Shaykewich et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its intrinsic importance in energy balance studies, net radiation is a key input variable in climatological models to assess evapotranspiration, and its precise estimate is essential for water resource management on regional scale RYU et al, 2008;PEREIRA et al, 2009;PEREIRA et al, 2011), for frost prediction studies, and air pollution monitoring (FRITSCHEN & FRITSCHEN, 2007).…”
Section: Introductionmentioning
confidence: 99%